Formal Education in Gold Coast-Ghana: An Overview of Colonial Policies and Curriculum from 1919 to 1927 - Ernestina Wiafe (Educational Considerations, 2021)
Prior to the arrival of Europeans in the 15th century, education existed in the Gold Coast (now Ghana) with the goal of introducing young people into the society by teaching children the traditions and values of the community, as well as the meaning of life. However, Great Britain, during colonization, implemented their own form of education within the Gold Coast. Great Britain thought it was their responsibility to bring the Gold Coast into the modern world by using education to lift the natives to a higher level of civilization. The Christian missionaries’ eagerness to propagate their faith through education and the British colonial governments’ educational policies, character-training curriculum, and desire to civilize natives, instead became a tool to achieve social control over the people of Gold Coast-Ghana which resulted in cultural annihilation, religious, and linguistic hegemony.
Keywords: Colonial government; Educational Policy; Curriculum; Formal Education